1995
DOI: 10.1271/bbb.59.1190
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility Characteristics of Isomaltooligosaccharides in Comparison with Several Saccharides Using the Rat Jejunum Loop Method

Abstract: Isomaltooligosaccharides (IMO) are a mixture of isomaltose, isomaltotriose, panose, isomaltotetraose, etc. IMO and its hydrogenated derivative (IMH) were characterized for their luminal clearance from rat jujunum loops as the indication of their digestibility. They were compared with a disaccharide fraction (IM2) and a higher oligosaccharide fraction (IM3) prepared from IMO, typical digestible saccharides (maltose, maltotriose, and sucrose), and typical nondigestible saccharides (maltitol, raffinose, and fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 6 publications
0
42
0
Order By: Relevance
“…From the results of luminal clearance from rat jejunum loops, Kaneko et al (1995) demonstrate that IMO is slowly digested (Kaneko et al, 1995). However, panose and isomaltotriose, which are the main components of IMO, are readily hydrolyzed in in vitro assay using rat small intestinal enzymes (Oku, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…From the results of luminal clearance from rat jejunum loops, Kaneko et al (1995) demonstrate that IMO is slowly digested (Kaneko et al, 1995). However, panose and isomaltotriose, which are the main components of IMO, are readily hydrolyzed in in vitro assay using rat small intestinal enzymes (Oku, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out by Kaneko et al (1995) using rats demonstrated that IMO was digested slowly in the jejunum and that components with a higher DP were less digestible and that the hydrogenated derivative of IMO was nondigestible. As such, it enters the colon in variable amounts.…”
Section: Criterion 1: Resistance To Gastric Acidity Hydrolysis By Mamentioning
confidence: 99%
“…Inulin-type fructans Coppa, Bruni, Zampini, Galeazzi, and Gabrielli (2002), Franck (2002), Roberfroid (2002), Roberfroid (2005) TOS Bouhnik et al (1997, Crittenden and Playne (1996), Vandenplas (2002) Lactulose Ballongue et al (1997), Gibson and Angus (2000) IMO Kaneko et al (1995), Kohmoto et al (1991) Lactosucrose Ohkusa et al (1995), Playne and Crittenden (1996) Xylooligosaccharides Crittenden and Playne (2002), Yamada (1993) SOS Crittenden and Playne (1996), Hayakawa et al (1990), Jaskari (1998) Glucooligosaccharides Chung and Day (2002), Djouzi et al (1995) Carbohydrates Chen et al (2002), Kanauchi (2003), Murphy (2001) The ecological consideration has significance for the safety of prebiotics (Hammes & Hertel, 2002). With regard to their safety evaluation, one has to consider the inherent properties of the prebiotic compound as well as their effects on the microbial flora altogether.…”
Section: Prebiotics Referencesmentioning
confidence: 99%